Work in progress: A blended mobile learning context oriented model applied to an information systems undergraduate degree curriculum. - Moreira, Fernando (2013)
The increasing number of mobile devices on day-to-day of the general population and particularly among youth people, leads to the emergence of new paradigms in several areas of activity, particularly in education. As an example of a new paradigm in the teaching / learning process can be invoked the mobile learning, such as technologies did not stop and progressed to become part of the Blended Mobile Learning (BML) model. In this paper and in the context of three-year courses Bologna Process European Degree structure at school, in Portugal, following the Curriculum Guidelines for Undergraduate Degree in Information Systems from ACM/AIS, we intend to test Mobile Google Docs system in our BML Context Oriented (BML-CO) model into an Information System course.